2017
DOI: 10.1007/s00417-017-3595-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined VEGF and PDGF inhibition for neovascular AMD: anti-angiogenic properties of axitinib on human endothelial cells and pericytes in vitro

Abstract: Axitinib inhibits angiogenesis in endothelial cells and pericytes via VEGFR and PDGFR modulation in vitro. Further studies are needed to elucidate whether axitinib may also improve therapy of CNV in AMD in vivo by interference with pericyte stabilization of pathological vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…Studies using PDGF inhibitors (such as Fovista and Axitinib), alone or in combination with other therapies, uncovered outcomes that might be useful for guiding management of ocular neovascularization [ 14 , 15 ]. In vitro, Axitinib was shown to modulate VEGFR and PDGRF and inhibit endothelial cells angiogenesis [ 16 ]. However, recent reports found no benefits with adding Fovista and Rinucumab (an anti-PDGFRβ antibody) to anti-VEGF therapy in neovascular AMD, causing the scientific community to reassess the role of PDGF in ocular angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using PDGF inhibitors (such as Fovista and Axitinib), alone or in combination with other therapies, uncovered outcomes that might be useful for guiding management of ocular neovascularization [ 14 , 15 ]. In vitro, Axitinib was shown to modulate VEGFR and PDGRF and inhibit endothelial cells angiogenesis [ 16 ]. However, recent reports found no benefits with adding Fovista and Rinucumab (an anti-PDGFRβ antibody) to anti-VEGF therapy in neovascular AMD, causing the scientific community to reassess the role of PDGF in ocular angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Nakano et al 31 found that type 1 CNV show significantly lower vessel junction densities than type 2 CNV on OCT-A, suggesting type 1 CNV to represent more mature vessels. Due to the associated pericyte coverage, mature type 1 CNV are less prone to degradation by VEGF inhibition 32 . In this context, it might be beneficial to adjust anti-VEGF dosing to prevent CNV type 1 into type 2 conversion, while the persistence of supportive type 1 CNV and their biomarker SRF might be tolerable.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB is the predominant isoform of the PDGF family expressed in the eye [ 28 ]. VEGF and PDGF have a synergic effect on vascular homeostasis [ 29 , 30 ]. In the second part of our study, we found that microglia stimulate VEGF-A and PDGF-BB expression in, and secretion from, RMECs, with an even stronger effect induced by activated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, migration, and proliferation are the most representative indices of endothelial cell function. The angiogenic growth factors VEGF and PDGF can enhance endothelial angiogenesis, migration, and the proliferation [ 30 , 39 41 ]. We showed that microglia promoted tube formation, wound healing, and proliferation of co-cultured RMECs, and activated microglia significantly enhanced these effects, in accordance with increased VEGF and PDGF levels.…”
Section: Discussionmentioning
confidence: 99%